Evaluation of the efficiency of corticosteroids in treating adult with sepsis: A protocol for systematic review and meta-analysis. Issue 18 (7th May 2021) - Li, Ke-Peng; Zeng, Yan-Yan; Li, Li-Li; Wang, Wan-Peng
Abstract: Background: Sepsis is a worldwide health problem that is a leading cause of mortality due to infection. Sepsis is prevalent in infections that are complicated with organ failure. Generally, sepsis is intricate and impaired corticosteroid metabolism leads to complex outcomes. Therefore, the provision of corticosteroids could lead to improved clinical outcomes. The effect of corticosteroids therapy in adult patients with sepsis is not well studied. Therefore, this study is an attempt to evaluate the efficacy of corticosteroids for treating adult cases of sepsis. Methods: We will systematically search the randomized controlled trials for potential eligible studies from online databases, which includes 5 English databases (PubMed, EMBASE, Web of Science, PsycINFO, and Cochrane Library) and 4 Chinese databases (China National Knowledge Infrastructure, WanFang Database, VIP information database, and China Biomedical Database) from their origin to March 2021. Languages were restricted to English and Chinese. Two independent authors will be screening the literature, collect, and perform data extraction and quality assessment. Data will be synthesized using appropriate statistical methods. Results: This study will summarize present evidence to evaluate the efficacy of corticosteroids for the treatment of adult cases of sepsis. Conclusion: The results of the present study will provide the latest, reliable, superior quality evidence for the clinical application of corticosteroids for treating sepsis patients. Ethics and dissemination: The present study will use published data and does not require ethics approval. Protocol registration number: March 28, 2021.osf.io/tm6sw. (https://osf.io/tm6sw/ )